SYSTEM OF PROSODY AS A SUBSYSTEM OF LANGUAGE (BASED ON THE MATERIAL OF THE CHINESE LANGUAGE) - M.A. Nurmukhamedova (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article describes in detail the role of supersegmental prosodic elements in the Chinese language, as a subsystem of language components. In addition, a connection is established between different theories regarding units of the segmental level of the Chinese language.